Pengembangan Aplikasi Mobile Location Based Service Berbasis Android Untuk Pencarian Lokasi Rumah Sakit Di Kota Malang Berdasarkan Asuransi Kesehatan Dengan Metode Agile System Development - Sabil Prihastomo Seputro; Herman Tolle; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Malang City is one of the big cities in East Java and its health development began to develop every year, and one of the health service that widely available is hospital. Now, people in Malang City can get treatment to the hospital easily with the existence of health insurance. But with the existence of various kinds of health insurance causes various troubles. People who own one kind of the health insurance confused when they want to search the hospital that received their health insurance because not all of the hospital will received all health insurance. People who were in emergency situation and require doctor attention immediately must find the nearest route to the hospital. If the targeted hospital does not receive their health insurance and the handling is late, it will be fatal and may even lead to death. To decrease those impact, people must able to search the hospital based on health insurance and routing from user location to the hospital location, with making an application that using GPS & API Google Maps with Agile System Development method that implemented on Android. The creation of Hospital Locator application intends to know the performance of each functional of the system, then it will be tested through validity testing as well as be testing with usability testing in the form of usability score and Likert scale to know the quality of the system. The result of the validity testing obtained that the functional of the system has been running well with 100% success rate. The result of the usability testing, the system gets score 92,91% which can be categorized as an A and user can operate the system easily and feel helpful about it.